Michael Raedecker : extract. - Ashton, Edwina; Debbaut, Jan; Ellis, Patricia; Stedelijk Van Abbemuseum, Eindhoven (Eindhoven : Stedelijk Van Abbemuseum, 2000)
The abandoned landscapes, empty interiors and mug-shot portraits of the Dutch artist Michael Raedecker appear to comply with the classical genres of painting landscapes, interiors and portraiture. But more than anything else his paintings possess a cinematic quality. Raedecker achieves this effect by carefully framing his image, using a technique that corresponds with the camera angles known from the film world : the long shot, interior shot and close-up in addition, although his works refer to places or scenes that seem familiar, the ultimately manage to escape any exact interpretation. The unique character of Raedecker's paintings is inherent in the way they are made. Besides very thinly applied and thickly Poured Out globs of paint, Raedecker makes use of threads and embroidery. This, in combination with a very specific, rather unwordly use of colour gives Raedecker's paintings a character all their own. This publication presents a first look at Raedecker's work from the recent years. In addition to numerous colour reproductions, the catalogue contains an introduction to the work by Edwina Ashton and a story related to Raedecker's work by Patricia Ellis.
Michael Raedecker : extract, Stedelijk Van Abbemuseum, Eindhoven, 13 November 1999 - 9 January 2000
biog., ind. tent. gr. tent., bibliog. p. 43-44
Engels
boek
Keywords: Raedecker, Michael